Fast and efficient preparation of three-arm star block copolymers via tetrazine ligation - Bakirdogen, Gulsah; Kahveci, Elif L. Sahkulubey; Kahveci, Muhammet U. (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
The inverse Electron Demand Diels-Alder (IEDDA) reaction between tetrazine and trans-cyclooctenol (TCO) is a fast and effective method employed to connect two or more molecules. In this study, an efficient and fast methodology based on tetrazine/trans-cyclooctene IEDDA reaction was developed for preparation of star-shaped block copolymers. Three-arm star polylactide-b-poly(ethylene glycol) (PLA-b-PEG) was chosen as a model system to show efficiency of the approach. First, three-arm PLAs with two different molecular masses were synthesized in a typical ring opening polymerization and functionalized with tetrazine end functionalities. while TCO end functionalized PEGs in two different molecular masses were perpared. Exact stoichiometric IEDDA click reaction between tetrazine moieties on three ends of the star polymer (s-3PLA-Tz) in the core and trans-cyclooctene (TCO) moieties of the periphery polymer (PEG-TCO) was performed in high click efficiency (up to 95.8%) in a short period (after 50-75 min). Ligation of PEG was confirmed by UV-vis, NMR and FT-IR spectroscopies, and size exclusion chromatography (SEC) and differential scanning calorimetry (DSC) analyses. In this way, various copolymers of desired architectures can be prepared in a short time and in high efficiency.
Keywords: Click chemistry; IEDDA; Tetrazine; Polylactide; Star polymer; Block copolymer; FREE CLICK CHEMISTRY; POLYMER; NANOPARTICLES; GLYCOL); SURFACE; Polymer Science